Depression and self-Concept in institutionalized and non-instituionalized children - Raffo Benavides, Luis. F. (1994)
This article reports a research on depression and self-concept in Peruvian children exposed ro negarive socioafective situations. Ir emphasizes the importance and specific characteristics of depression both from a psychological and clinical point of view. The sample consisred ofboys between 8 and 14 years old, 35 institutionalized, 30 from a marginal district of Lima and 20 with a depression diagnosis. The objective of the study was ro analyse the correlation between both variables, compare rhe scores in the three groups, and the adaptation of the CDI (Children Depressive Inventory, Kovacs, 1983}. Results show a signifcative negative correlation between depression and self-concept. Ir is found that institutionalization and low SES influence the degree of depression, however, ir has less importance in self-concept. The instruments are valid and reliable.